Investigating Learning Obstacles In Mathematical Literacy: A Study On Linear Equations With One Variable - Rayhan, Nabila Cynthia; Suryadi, Didi; Hasanah, Aan (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
The topic of linear equations with one variable is studied at the junior high school level. This topic is essential as it can be applied to solve various real-life problems. However, many students struggle to master this concept, often due to various learning obstacles. This study aims to describe the learning obstacles faced by students in understanding linear equations with one variable in the context of mathematical literacy. The method of research used is a descriptive method with a qualitative approach. The research subjects were six eighth-grade students from a junior high school in Bandung. Data were collected through written tests and interviews. The results revealed five types of learning obstacles related to the material of linear equations with one variable based on mathematical literacy. These obstacles include: difficulties in forming equations, inaccuracy in reading or understanding questions, and challenges in concluding. Additionally, students faced difficulties in understanding the relationships between different concepts and in understanding what needs to be done. To overcome these learning obstacles, several efforts can be made, including transforming abstract concepts into concrete and visual representations, improving interactive and contextual problem-based teaching methods, and offering varied exercises. These strategies are expected to significantly enhance students' mathematical literacy and reduce learning obstacles.